Adoption and Promotion of Resilient Crops for Climate Risk Mitigation and Import Substitution: A Case Analysis of Cassava for South African Agriculture - Amelework, Assefa B.; Bairu, Michael W.; Maema, Obakeng; Venter, Sonja L.; Laing, Mark (Frontiers in Sustainable Food Systems, 2021)
Cassava is an important starchy root crop grown mainly in the tropical and subtropical regions of the world. The ability of cassava to withstand difficult growing conditions and long-term storability underground makes it a truly resilient crop for food and nutrition security. South Africa's interest in cassava cultivation is very recent, with the emphasis mainly on production of high quality starch on an industrial scale and as a climate change mitigation strategy. Historically, smallholder farmers have grown cassava as a minor crop in the far north-eastern part of the country. However, there is a national initiative to evaluate the crop’s potential with the following objectives: to examine the potential of cassava as a climate change adaptation strategy for food and industrial use; to explore the potential of cassava starch for import substitution; and to identify viable business opportunities for smallholder farmers from the production of cassava in South Africa. In this scoping study, production, processing and marketing data for cassava were accessed from the FAO and US Commercial trade databases. Other domestic market and demand analysis case studies were also explored. The study indicated that South Africa imports more than 66,000 tons of starch annually, of which 33% is cassava starch, showing the availability of a local market. The environmental and socio-economic significance of cassava to the South African economy is discussed. The results indicate that significant business opportunities exist for the use of cassava in South Africa. However, the realisation of these opportunities will depend on the reliable supply of good quality cassava. The study pointed out that the lack of a well-established cassava R&D program and under-developed value chains will have a significant impact in the development of cassava industry in the country. The development of strong value chains is vital in order to integrate cassava into the starch market. However, this will only occur if high potential germplasm is imported, characterized and bred for local conditions to ensure the sustainable primary production of cassava.